Two new species of Tachyphyle Butler, 1881 from South America (Lepidoptera: Geometridae) - J. Viidalepp; A. Lindt (SHILAP)
The Neotropical emerald geometrid genus Tachyphyle Butler, 1881 as revised by PITKIN (1996), consists of fifteen described species. This article is aimed at presenting descriptions of two additional species, Tachyphyle nielseni Viidalepp & Lindt, sp. n. from Argentina which is similar to T. acuta Butler, 1881 and Tachyphyle selini Viidalepp & Lindt, sp. n. from Costa Rica and Ecuador, which is similar with T. undilineata (Warren, 1900). The adults and their male genitalia are illustrated